Intratumoral Brevibacillus parabrevis enhances antitumor immunity by inhibiting NK cell ferroptosis in hepatocellular carcinoma - Banglun Pan; Xiaoxia Zhang; Dongjie Ye; Yuxin Yao; Zhu Zhang; Yue Luo; Hao Wu; Xiaoqian Wang; Nanhong Tang (Cell Death and Disease)
Abstract It is known that intestinal flora affects the number and function of NK cells through metabolites, thereby regulating the response of tumors to chemotherapy or immunotherapy. However, little is known about whether intratumoral bacteria are involved in NK cell-mediated antitumor immunity. In this study, 2bRAD-M analysis was performed on patient hepatocellular carcinoma and paired tissues to determine the composition of the intratumoral microbiota. Mass cytometry, flow cytometry, co-immunoprecipitation, immunoblotting, immunofluorescence, and DNA pull-down assays were used to evaluate the relationship between intratumoral bacteria, ferroptosis, and NK cell activity in Hu-SRC mice. Here, we found that the intratumoral B. parabrevis inhibited NK cell ferroptosis by promoting lipolysis into acetyl-CoA. Mechanistically, B. parabrevis catalyzed the acetylation of RORC, enhancing its binding to the NEDD4L promoter. NEDD4L induced ubiquitination of iron transporters SLC39A14, SLC39A8, and STEAP3. Functionally, B. parabrevis induced NK cells to differentiate into adaptability, cytotoxicity, and heat shock phenotypes, inhibiting the terminal phenotype and changing the tumor microenvironment from “cold” to “hot”. In conclusion, B. parabrevis enhanced the antitumor response of NK cells by regulating post-translational modifications. Our study identified a new strategy for utilizing intratumor bacteria for clinical treatment.